Metabolic activity and community structure of prokaryotes associated with particles in the twilight zone of the South China Sea - Liu, Hao; Wang, Fangzhou; Liu, Hongbin; Jing, Hongmei (Frontiers in Microbiology, 2022)
The twilight zone is an important depth of the ocean where particulate organic matter (POM) remineralization taken place, and prokaryotes contribute to more than 70% of the estimated remineralization. However, little is known about the microbial community and metabolic activity associated with different particles in the twilight zone. The composition and distribution of particle-attached prokaryotes in the twilight zone of the South China Sea (SCS) were investigated using high-throughput sequencing and quantitative PCR, together with the Biolog EcoplateTM microplates culture to analyze the microbial metabolic activity. We found that α- and γ-Proteobacteria dominating at the lower and upper boundary of the twilight zone, respectively; Methanosarcinales and Halobacteriales of the Euyarchaeota occupied in the larger particles at the upper boundary. Similar microbial community existed between euphotic layer and the upper boundary, which were continuously connected with similar water chemistry. Relatively stable higher microbial community in the larger particles along the water depths, might be due to the fast sinking and major contribution of carbon flux of the larger particles from the euphotic layer. Except polymers as the major carbon source, carbohydrates and amino acids were preferentially used by samples at the upper and lower boundary, respectively. This could potentially be attributed to the metabolic capabilities of attached microbial groups in different particles, and reflected the initial preference of the carbon source by the natural microbes in the twilight zone as well. The microbial structure and carbon metabolic profiles could be complemented with metatranscriptomic analysis in future studies to augment the understanding of the complex carbon cycling pathways in the twilight zone.